ANALYSIS AND DESIGN OF LOW COST INFORMATION COMMUNICATION AND TECHNOLOGY - BASED APPLICATION SOFTWARE FOR SUSTAINABLE TOURISM DEVELOPMENT IN AFRICA: NIGERIA AS A CASE STUDY - Asafe, Yekini Nureni; Olanrewaju, Ojo; Adeyemi, Okunlola Gabriel; Bolanle, Dada (European Scientific Journal, ESJ, 2013)
The paper conducts an investigative study into the uses and applications of information and communication technology (ICT) for sustainable tourism development (STD) with particular reference to security control and management in tourist centres across Nigeria. The researcher collected data to measure level of adoption and usage of ICT within tourist centres in Lagos State. The analysis of the data collected leads to proposition of Low Cost ICT- Based Application Software which can be used to control and manage security in tourist centers across Nigeria.